FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU MAKAN PADA ANAK GIZI LEBIH DI SEKOLAH MENENGAH PERTAMA WILAYAH KERJA PUSKESMAS PONCOL KOTA SEMARANG - Farah Husna Fadhilah; Bagoes Widjanarko; Zahroh Shaluhiyah (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Excess body weight in school children is a worrying problem because it could cause illness and lower self confidence. Increased prevalence of excess nutrition in school children at junior high school was 5,5% caused by many factors like bad eating habit and environmental condition such as peer role, parents, teacher and availability of infrastructure will affect chidren eating behavior. This research was using quantitative apprach with cross sectional design. Samples of the research were using simple random sampling technique with total samples of 81 male and female students with excess nutrition with BMI 23-29,9 kg/m2 in grade VII, VIII, IX in Junior High School at working areas of Poncol Health Center. Data was collected by interviewing with questionnaire. Data was analyzed using univariate and bivariate. Most of the respondents were 14 years old (39,5%) with the most age category of 12-14 years old (79%), majority of the respondents were females (51,9%) with Basal Metabolic Index classified as obesity (50,6%). Majority of the respondents had bad eating behavior (72,8%). The results of chi square test showed that respondents knowledge towards eating behavior (p=0,021), respondents attitude towards eating behavior (p=0,002), availability of infrastructure affecting eating behavior (p=0,000), parents role (p=0,000), and peer role (p=0,003) were significantly correlated with eating behavior in excess nutrition students. While age (p=0,144), sex (p=0,767), Basal Metabolic Index (p=0,286), and teacher role (p=0,286) were not significantly correlated with eating behavior of JHS students with excess nutrition. This research recommended to maintain eating behavior in order to be spared of obesity and prevent increased of body weight.